A Survey of Food Delivery Innovation Evolution in Developing Countries: Insights from Indonesia - Yasirandi, Rahmat; Thanasopon, Bundit (My University, 2023)
The food service industry is one of the most promising businesses today, and the availability of food delivery is one of the digital transformations that has occurred in this industry. The continuous development of innovation in this business promises to increase success and revenue. This research examines how food delivery is one of the innovations that plays a crucial role in the sustainability of restaurants/food merchants. The exploratory scope in this survey study is based on research questions, starting with the process evolution in food delivery over time. This includes the influence of three technological eras: cellular telephones, websites, and mobile operating systems, which have an evolutionary impact on the business concept point of view, from restaurant-based delivery to the emergence of e-commerce. The research also explores the benefits and challenges that arise during adoption, with 5 benefits identified, including improved customer experience, increased order efficiency, increased order flexibility, improved food control, and crisis management. The challenges that arise during adoption include inconsistent delivery and quality, technology dependency, partnership dissatisfaction, and health and environmental issues. Based on the findings of this study, there is an opportunity to design a technology adoption model for online food delivery in Indonesia in the future.
Keywords: developing countries; food delivery; Indonesia; restaurant